2001
DOI: 10.1046/j.1365-2109.2001.00573.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary protein and energy levels on growth, oxygen consumption, haemolymph and digestive gland carbohydrates, nitrogen excretion and osmotic pressure of Litopenaeus vannamei (Boone) and L. setiferus (Linne) juveniles (Crustacea, Decapoda; Penae

Abstract: The influence of protein and energy levels on growth rate, survival, pre‐ and post‐prandial oxygen consumption, ammonia excretion, haemolymph glucose (HG), glycogen in digestive gland and osmotic pressure (OP) in white shrimp Litopenaeus vannamei (Boone) and L. setiferus (Linne) juveniles was studied. Diets containing a high‐quality protein at a protein/energy (P/E) ratio of 16, 26, 31 and 36 mg kJ−1 were fed at 20% of shrimp body weight of two sizes: < 1 g and > 1 g. Both species showed a optimum P/E ratio of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
44
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 37 publications
(72 reference statements)
9
44
1
2
Order By: Relevance
“…However, techniques to determine immunity are much less well developed for invertebrates. In this context, it has been suggested that blood proteins and haemocyanin levels together with some additional blood metabolites could act as good indicators of health status, Rosas et al (2001). In the present study, examination of protein proWles using SDS-PAGE gels did not reveal any marked diVerences between samples of fractionated haemolymph produced from control and Egrosan treated shrimp.…”
Section: Discussionmentioning
confidence: 69%
“…However, techniques to determine immunity are much less well developed for invertebrates. In this context, it has been suggested that blood proteins and haemocyanin levels together with some additional blood metabolites could act as good indicators of health status, Rosas et al (2001). In the present study, examination of protein proWles using SDS-PAGE gels did not reveal any marked diVerences between samples of fractionated haemolymph produced from control and Egrosan treated shrimp.…”
Section: Discussionmentioning
confidence: 69%
“…Fish intestine, due to its high polyunsaturated fatty acids content (up to 24.9% of total fatty acid composition), is susceptible to the attack of reactive oxygen species (ROS) (Khoddami et al, 2009;Ji et al, 2011). Intestinal ROS can be produced from endogenous sources, such as from aerobic metabolism, muscle movement of intestine and inflammatory cell activation (Datta et al, 2012;Martin et al, 2012;Rosas et al, 2001) and exogenous sources, including the diet and environmental stress (Jiang et al, 2011;Sanders et al, 2004). Increased ROS can result in lipid peroxidation and protein oxidation in cells, thus disturbing the integrity of fish intestinal epithelial cells (Chen et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Rosas et al (2001) Rasio energi dan protein pada pakan uji sekitar 8%. Hal ini menggambarkan keseimbangan antara jumlah protein dan energi.…”
Section: Uji Kimiawiunclassified